Can community as a whole be a client for nurses? - Pedro Melo; Manuela Fonseca (Archives of Nursing Practice and Care - Peertechz Publications, 2020)
Community Health Nursing and Public Health Nursing has a long history in the world. However, most of the times it is associated to care in community more than care to community [1].